The role of non-alcoholic fatty liver disease in the formation of atherosclerotic vascular lesions in patients with abdominal obesity - N. L. Denisov; V. B. Grinevich; Ye. V. Chernetsova; Yu. A. Kravchuk; K. V. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of investigation. To study the vascular wall changes of common carotid artery and internal carotid arteries in patients with abdominal obesity (AO) and different forms of nonalcoholic fatty liver disease (NAFLD). Material and methods. The study involved 60 patients with AO (waist circumference ≥80 cm in women and ≥94 cm in men) and NAFLD who provided written informed consent to participate in the study. The age of the patient ranged from 18 to 59 years. Patients’ symptoms, past history, were evaluated to exclude alcoholic or drug-induced liver disease, anthropometric parameters were studied. All patients underwent a complex of laboratory and instrumental tests required by the Russian guidelines for diagnosis and treatment of NAFLD (2015). Severity of pathological changes in the liver tissue (fibrosis and steatosis) was assessed by noninvasive Steatoskrin diagnostic method (Biopredictive laboratory, France). Measurement of the intima-media complex thickness of the common carotid artery (IMT CCA) was performed by standard procedures at Voluson 730 Expert device, equipped with 7,5 MHz linear phased array transducer. The presence of early atherosclerotic markers was evaluated by local thickening of the IMT CCA over 0.86 mm in any point of the carotid artery (IMT CCA max). The data were processed by comparative and correlation analysis. Results. The relationship between the presence of NAFLD, initial manifestations of atherosclerosis and insulin resistance was established. This resulted in the rank of prognostic factors based on severity of carotid artery changes, making it possible to conclude individual atherosclerotic risk score for AD and different forms of NAFLD. Conclusion. The results of the study require more profound examination of patients with NAFLD to evaluate both liver and cardiovascular diseases risk.